Attractiveness of a financial centre : a comparison of Hong Kong and Singapore on investment factors. - Lim, Henry Shien Ching. (2009)
The purpose of this project is to examine the factors that attract global investors to invest in either Singapore or Hong Kong. Respondents were asked to give their perception of Singapore and Hong Kong in relation to 11 factors and to assess the relative importance of these factors when making investment decisions.